METODE PENGENALAN MEMBACA YANG MENYENANGKAN PADA ANAK USIA DINI - Mutmainah Mutmainah (MAJALAH ILMIAH PEMBELAJARAN, 2009)
The first three years in children’s life is the most sensitive period whichwould determine children’s brain development and their future life. The introductionof alphabetical for children could be better done non formally by story telling. Themore complex of alphabetical can be introduced for children by the age of 2 years.We can ask the children to name the alphabetical that we showed them. Then, we canimprove this exercise by asking them to read word by word. In order to make theexercises (alphabetical introduction and reading the words) are easy to be followed bychildren, parents should understand how to deliver the exercises properly to thechildren.Mothers have a significant role to optimize children’s development. Theyneed to give a special attention and time everyday to interact with children usingsome activities which are effective for children intelligence’s development, withoutbeing interrupted with any other activities. One of the example of those activities isby cutting some interesting pictures, could be animal, from magazines or books, thenmake those pictures as flash cards to be showed to the children. This would have ahuge impact for the children’s learning. A working parent needs to monitor and givethe correct direction to their nanny or baby sitter about the learning activities whenthey are not home. It’s simply by making the list of activities so that the baby sittersknow what to do everyday to stimulate children’s intelligence development, bothintellectual, emotional and their social and physical development. Don’t let the babysitters to baby sit the children without giving them the stimulations which aresignificant for children.Some technique that could be used for the reading introduction are using thealphabetical, introducing through things, Montessori School, Finger Painting, GamesFor Learning, Kinderland method, Flash Card, Story Telling, alphabetical carpet,learning to typing, finishing the incomplete words, and alphabetical posters as thedecoration.